Pendidikan Multikulturalisme Analisis Terhadap Nilai-Nilai Pendidikan Q.S. Al-Baqarah Ayat 62 dan Al-Hujurat Ayat 10,11,12 dan 13 - Rahman, Syaifur (At- Ta'lim : Jurnal Pendidikan, 2018)
Horizontal conflicts are unrelenting in the community. The trigger is the weakness of the diversity foundations of the community so that they tend to have a monocultural or uniform mindset. In this case religion plays an important role because religion is always used as a source of truth doctrine to legalize certain actions that sometimes break through the limits of human values.Indonesia which in fact is a country with millions of tribes facing serious problems if its young generation has no understanding of diversity. Therefore, multicultural education is needed to strengthen the foundation of nationality in the present and the future. In this case education is expected to have a solution to prepare a generation that has an understanding of multicultural understanding of addition to upholding one's own culture must also respect the culture of others, in addition to having confidence that should always be glorified he must also respect the beliefs of others different.Religion as one of the references in human life always provide solutions for the realization of happiness in human life. Without exception the diversity of religion in human life, all have been explained. One of them is explained in the 62nd verse of Q.S.al-Baqarah which explains that as long as the followers of those religions believe God as their Lord, they have the equality in the promise of Allah in the last day. Keywords: Horizontal conflicts, monocultural, diversity, Q.S.al-Baqarah